2021
DOI: 10.3390/v13081614
|View full text |Cite
|
Sign up to set email alerts
|

The Repressor C Protein, Pf4r, Controls Superinfection of Pseudomonas aeruginosa PAO1 by the Pf4 Filamentous Phage and Regulates Host Gene Expression

Abstract: It has been shown that the filamentous phage, Pf4, plays an important role in biofilm development, stress tolerance, genetic variant formation and virulence in Pseudomonas aeruginosa PAO1. These behaviours are linked to the appearance of superinfective phage variants. Here, we have investigated the molecular mechanism of superinfection as well as how the Pf4 phage can control host gene expression to modulate host behaviours. Pf4 exists as a prophage in PAO1 and encodes a homologue of the P2 phage repressor C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…A significant decrease in pyoverdine production was observed in both lysogenic strains. Similarly, the PAO1 mutant in the absence of Pf4 prophage was shown to produce significantly more pyoverdine than its wild-type [69]. The results obtained for P. aeruginosa exopigment production suggest that the Pf4 decreased toxicity of the examined strains.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A significant decrease in pyoverdine production was observed in both lysogenic strains. Similarly, the PAO1 mutant in the absence of Pf4 prophage was shown to produce significantly more pyoverdine than its wild-type [69]. The results obtained for P. aeruginosa exopigment production suggest that the Pf4 decreased toxicity of the examined strains.…”
Section: Discussionmentioning
confidence: 82%
“…Infection by Pf4 phages severely inhibited pyocyanin production of lysogenic strains. Ismail et al, (2021) [69] demonstrated that PAO1 without Pf4 phage produced less pyocyanin compared to wild-type after 24 h of incubation. Although it seemed that Pf4 stimulated pyocyanin production in its original host, it decreased pyocyanin production in PA14 and LESB58 P. aeruginosa strains.…”
Section: Discussionmentioning
confidence: 99%
“…Prophage also can also modify their hosts in ways that alter their capacity for horizontal gene transfer (HGT). Prophage protect against superinfection by competing phages, including unrelated lytic phages (27, 60, 69) thereby blocking transduction and also modulate, and concurrently block conjugation through the same modifications of Type IV secretion, which has been shown both in phage M13 (70) and for Pf4 of Pseudomonas aeruginosa (51, 52). The concept that prophage conferred immunity contributed to ST36 population succession is attractive considering DNA release by predation of non-lysogen susceptible hosts can promote transformation through natural competence (7173), and phage transduction and conjugation mediated by Type IV secretion also facilitate horizontal gene transfer (HGT) all of which could drive rapid diversification such as observed in the native ST36 population (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A distinctive feature of Pf4 phages released in PAO1 during biofilm formation is their ability to reinfect the PAO1 host, which is known as superinfection (Webb et al ., 2003; Webb et al ., 2004; Rice et al ., 2009; Hay and Lithgow, 2019). The superinfectivity of Pf4 phages released in PAO1 during biofilm formation is related to mutations in the phage repressor regions (McElroy et al ., 2014; Ismail et al ., 2021). Superinfection exclusion is important for the development of resistance against superinfective phage virions in PAO1 host cells; however, the mechanism of superinfection exclusion has not been well studied.…”
Section: Introductionmentioning
confidence: 99%